Answer:
x = 1, y = -1
Explanation:
If we have the two equations:
and
, we can look at which variable will be easiest to eliminate.
looks like it might be easy to get rid of, we just have to multiply
by 2 and y is gone (as -6y + 6y = 0).
So let's multiply the equation
by 2.
![2(4x + 3y = 1)\\8x + 6y = 2](https://img.qammunity.org/2021/formulas/mathematics/college/xmu75xevukpl54279ugq3jic3edwb374ob.png)
Now we can add these equations
![8x + 6y = 2\\-3x-6y=3\\](https://img.qammunity.org/2021/formulas/mathematics/college/rywv3vdn1huhqf4h1gnl2e1dd7oh3pd47m.png)
------------------------
![5x = 5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/q6e9he0jj2wqjintygth74hivz69r46apr.png)
Dividing both sides by 5, we get
.
Now we can substitute x into an equation to find y.
![4(1) + 3y = 1\\4 + 3y = 1\\3y = -3\\y = -1](https://img.qammunity.org/2021/formulas/mathematics/college/mxx8lgwqeyjo05jxtvmga23nlnxfnc0gxj.png)
Hope this helped!